2020
DOI: 10.1088/1755-1315/596/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Optimization And Kinetic Analysis On The Production Of Hyaluronic Acid By Streptococcus Zooepidemicus In A Batch System

Abstract: In this study, the optimization and kinetic analysis on the effect of process parameters for the production of hyaluronic acid production by S. zooepidemicus were performed in batch system. The fermentation condition such as inoculum size (2 to 20 %), pH (4 to 10), temperature (30 to 45) and agitation (50 to 500) were optimized using “one-factor-at-a-time” method. It was found that the inoculum size of 10 % had the greatest effect on the fermentation process which gave the highest value of specific growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In addition to the pH, the incubation temperature, agitation speed, soil composition, and size of inoculum are key parameters of the fermentation process that affect the yield of the final product. Some researchers found that a streptococcal inoculum size of 10% had the greatest effect on the fermentation process and also that an agitation speed of 300 rpm could increase the HA yield [ 90 ]. This may have occurred because at this rate of speed, a greater subdivision of air bubbles could occur with a consequent larger surface area for the gas–liquid mass transfer, which therefore led to a reduction in the thickness of the gas and liquid films responsible for the resistance to the mass transport [ 90 ].…”
Section: Ha Fermentation Process In Engineered Host Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the pH, the incubation temperature, agitation speed, soil composition, and size of inoculum are key parameters of the fermentation process that affect the yield of the final product. Some researchers found that a streptococcal inoculum size of 10% had the greatest effect on the fermentation process and also that an agitation speed of 300 rpm could increase the HA yield [ 90 ]. This may have occurred because at this rate of speed, a greater subdivision of air bubbles could occur with a consequent larger surface area for the gas–liquid mass transfer, which therefore led to a reduction in the thickness of the gas and liquid films responsible for the resistance to the mass transport [ 90 ].…”
Section: Ha Fermentation Process In Engineered Host Microorganismsmentioning
confidence: 99%
“…Some researchers found that a streptococcal inoculum size of 10% had the greatest effect on the fermentation process and also that an agitation speed of 300 rpm could increase the HA yield [ 90 ]. This may have occurred because at this rate of speed, a greater subdivision of air bubbles could occur with a consequent larger surface area for the gas–liquid mass transfer, which therefore led to a reduction in the thickness of the gas and liquid films responsible for the resistance to the mass transport [ 90 ]. In this way, it is easy to understand that several parameters must be optimized in order to enhance the microbial production of HA starting from natural producer microorganisms.…”
Section: Ha Fermentation Process In Engineered Host Microorganismsmentioning
confidence: 99%
“…The type of microbe used in bio-production will determine the optimal temperature for generating polysaccharides like HA (Liu et al, 2018) and (Shoparwe et al, 2020).5.2.4. pH:One of the most crucial factors that must be managed in the majority of fermentation processes is the medium's pH. It has been demonstrated that pH has a greater impact on polysaccharide formation than on cell proliferation(Shoparwe et al, 2020). HA is particularly sensitive to pH fluctuations, where it was found that HA is broken down by hydrolysis at relatively basic (>11) or acidic (4.0) pH levels.…”
mentioning
confidence: 99%